ANALISIS PERCEPATAN PROYEK DENGAN METODE CRASHING PADA PEMBANGUNAN RUMAH KOMERSIL (STUDI KASUS : PROYEK PEMBANGUNAN 3 UNIT RUMAH TIPE 45 NEW AIYANA 2025, PALANGKA RAYA) - KEVIN FANI KRISTIAN (INFO-TEKNIK, 2025)
Delays in construction projects are a recurring issue in Indonesia, often resulting in budget overruns and reduced efficiency. This study analyzes a project acceleration strategy using the crashing method on a housing project consisting of three Type 45 residential units located in Palangka Raya, Central Kalimantan. The project was originally scheduled for 214 calendar days, with a contract value of Rp 557,639,742.03. Despite the relatively small scope, time constraints and a client request for faster delivery required optimization efforts. By applying descriptive quantitative methods, this research evaluated two crashing alternatives: adding working hours (overtime) and increasing labor. The study reviewed previous implementations of crashing methods and assessed their relevance to this case. Results show that accelerating the critical path can reduce project duration effectively while maintaining cost efficiency. The results of the crashing analysis using two alternatives—1-hour and 2-hour overtime additions—were compared based on efficiency in the crash activity of Batako Wall Installation (1PC:3PP). Between the two alternatives, the 2-hour overtime option was selected due to its higher time efficiency and negligible difference in cost efficiency compared to the 1-hour alternative. The 2-hour overtime alternative proved more effective given the significant reduction in overall project duration. It shortened the project by 6 days, from 215 calendar days to 209 days—resulting in a 2.7% time efficiency. The total project cost was reduced by Rp 3,597,896.45, from Rp 633,800,000.00 to Rp 630,202,103.55, yielding a 0.56% cost efficiency.